1) Найдем неизвестное слагаемое — (5 7/9 - х):
5 7/9 - х = 3 5/12 - 2 3/4,
5 7/9 - х = (3 - 2) + (5/12 - 3/4),
5 7/9 - х = 1 + (5/12 - 9/12),
5 7/9 - х = 1 - 4/12,
5 7/9 - х = 1 - 1/3,
5 7/9 - х = 2/3.
2) Вычислим значение вычитаемого — х:
х = 5 7/9 - 2/3,
х = 5 + (7/9 - 2/3),
х = 5 + (7/9 - 6/9),
х = 5 1/9.
3) Выполним проверку:
(5 7/9 - 5 1/9) + 2 3/4 = 3 5/12,
6/9 + 2 3/4 = 3 5/12,
2/3 + 2 3/4 = 3 5/12,
2 + (2/3 + 3/4) = 3 5/12,
2 + (8/12 + 9/12) = 3 5/12,
2 + 17/12 = 3 5/12,
2 + 1 5/12 = 3 5/12,
3 5/12 = 3 5/12.
ответ: х = 5 1/9.
Пошаговое объяснение:
Пошаговое объяснение:
4x + 12 = 3x + 8
4x - 3x = 8 - 12
x = -4
3x - 17 = 8x + 18
8x - 3x = -17 - 18
5x = -35
x = -35 : 5
x = -7
0,8y + 1,4 = 0,4y - 2,6
0,8y - 0,4y = -2,6 - 1,4
0,4y = -4
y = -4 : 0,4
y = -10
0,18x - 3,54 = 0,19x - 2,89
0,19x - 0,18x = -3,54 + 2,89
0,01x = -0,65
x = -0,65 : 0,01
x = -65
(2 2/5)x + 3 2/15 = (3 1/5)x + 2 1/3
(3 1/5)x - 2 2/5x = 3 2/15 - 2 1/3
(4/5)x = 3 2/15 - 2 5/15
(4/5)x = 12/15
x = 12/15 * 5/4
x = 1
1/4 - (1/3)m = 4 1/4 - 3m
3m - (1/3)m = 4 1/4 - 1/4
(2 2/3)m = 4
m = 4 : 2 2/3
m = 4 : 8/3
m = 4 * 3/8
m = 3/2
m = 1 1/2